Rotavirus diarrhea in hospitalized children under 5 years of age in Vientiane, Lao PDR, 2009–2015. Issue 51 (14th December 2018) - SoukAloun, Douangdao; Douangbouphaa, Vannida; Phetsouvanh, Rattanaphone; Sibounheuang, Bountoy; Vongsouvat, Manivanh; Chanmala, Keomany; Vongphachanh, Thonglay; Maniphonh, Soudalinh; Phouangsouvanh, Inhpanh; Fox, Kimberley; Logronio, Josephine; Grabovac, Varja; et al.
Abstract: Background: Diarrhea is a leading cause of death in children <5 years worldwide, causing an estimated 215, 000 deaths in 2013. This evaluation tracks the epidemiologic patterns and most common rotavirus genotypes among hospitalized children in this age group with acute gastroenteritis in Lao PDR. Methods: Children <5 years in a central tertiary hospital in the capital city were prospectively enrolled into the surveillance platform during January 2009—December 2015. We collected information regarding clinical characteristics of enrolled children. Stool samples were obtained within 24 h of hospital admission and tested for rotavirus using rotavirus antigen detection enzyme immunoassay. Samples were sent to the regional reference laboratories in Australia and South Korea for genotyping. Bivariate analyses compared demographic and clinical characteristics between rotavirus positive and negative children using Chi-square statistical testing. Seasonality of rotavirus and annual genotype distribution are also described. Results: We enrolled 1853 children <5 years with acute gastroenteritis during the surveillance period and collected 1772 fecal specimens, 982 (55%) of which tested positive for rotavirus. A higher proportion of rotavirus acute gastroenteritis was observed among children 12–23 months of age as compared to rotavirus negative children in the same age group, 41% vs 36%. Eighty-six percent of rotavirus positive children experienced vomiting, as compared to 65% of rotavirus negative children. Eighty-five percent (n = 830/982) of rotavirus positive specimens occurred during the dry season (January-April). The most common genotypes identified were G1, G2, G3 and P8 and P4. The most prevalent combined genotype differed annually during the surveillance period. Conclusion: Surveillance continues to be important in documenting the burden of rotavirus in children <5 years in Lao PDR as well as providing a baseline for determining the impact of rotavirus vaccine once it is introduced into Lao PDR's national immunization schedule.